Analisis Semiotika Nilai-nilai Islam dalam Film Budi Pekerti - Dzalfa Tsaltsa Kamilah; Rodliyah Khuza’i; Ida Afidah (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. The film "Budi Pekerti" was selected for analysis due to its portrayal of the phenomenon of ethical decline among individuals in both the physical and virtual realms. This research project aims to examine the manner in which Islam provides an explanation of human behaviour through the Qur'an and Hadith, and to analyse the storyline, semiotics and values present in the film. A qualitative method with a descriptive approach was employed, comprising observation, documentation, and a literature study. A semiotic analysis of the film revealed twelve scenes containing elements of semiotics, including dialogue, body language, and expressions. A semiotic analysis based on Charles S. Peirce's theory reveals the meanings conveyed in the film. The first scene illustrates the meaning of failure through the act of twisting fingers, while the second scene emphasises the significance of direct confrontation with the incident. The remaining scenes convey the meanings of introspection, gratitude, and reflection on death and communication. The Islamic values espoused in the film emphasise moral aspects, particularly those related to creed and sharia, which are relevant in certain contexts. Abstrak. Film "Budi Pekerti" dipilih dalam penelitian karena menggambarkan fenomena hilangnya etika masyarakat saat berinteraksi di dunia nyata maupun maya. Penelitian ini bertujuan untuk mengkaji bagaimana Islam menjelaskan perilaku manusia melalui Al-Qur’an dan Hadits serta menganalisis alur cerita, semiotika, dan nilai-nilai dalam film tersebut. Menggunakan metode kualitatif dengan pendekatan deskriptif yang melibatkan observasi, dokumentasi, dan studi literatur. Peneliti menemukan dua belas scene yang mengandung semiotika berupa dialog, gerakan tubuh, dan ekspresi. Analisis semiotika berdasarkan teori Charles S. Peirce menunjukkan makna-makna, seperti pada scene pertama menunjukkan makna kegagalan melalui memelintir jari, sementara scene kedua menunjukkan pentingnya melihat langsung kejadian. Kemudian Scene lainnya mengandung makna introspeksi, rasa syukur, serta refleksi tentang kematian dan komunikasi. Adapun nilai-nilai Islam yang terdapat dalam film ini lebih menekankan pada aspek akhlak, dengan akidah dan syariah yang relevan dalam konteks tertentu.